If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -6)(3x + -6) = 0 Reorder the terms: (-6 + 3x)(3x + -6) = 0 Reorder the terms: (-6 + 3x)(-6 + 3x) = 0 Multiply (-6 + 3x) * (-6 + 3x) (-6(-6 + 3x) + 3x * (-6 + 3x)) = 0 ((-6 * -6 + 3x * -6) + 3x * (-6 + 3x)) = 0 ((36 + -18x) + 3x * (-6 + 3x)) = 0 (36 + -18x + (-6 * 3x + 3x * 3x)) = 0 (36 + -18x + (-18x + 9x2)) = 0 Combine like terms: -18x + -18x = -36x (36 + -36x + 9x2) = 0 Solving 36 + -36x + 9x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '9'. 9(4 + -4x + x2) = 0 Factor a trinomial. 9((2 + -1x)(2 + -1x)) = 0 Ignore the factor 9.Subproblem 1
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {2, 2}
| Sin^3x=sinx | | (-4x^7y)(x^7y^2)= | | (xy)/(-4xy) | | 3x+5x+16x=180 | | 3x+5x+6x=180 | | g^2+13g=140 | | 30n^2+204n+144=0 | | (3-z)(3z-1)=0 | | 5x+15=7x+3-2x+12 | | 3x+6=9x-3(2x-2) | | 8(x+4)-4=4X+1 | | 4(5-m)=36 | | 6-(4x-5)= | | 5h=18.59-5h | | 2(w+7)+2w=210 | | 2x+6x+10=34 | | 5h+(18.59-5h)=h | | x^2-9x-130=0 | | 5h+(18.59-5h)=18.59 | | log(9)+log(x)=0 | | n=-3x^2-4x+5 | | (y-8)(y-8)=0 | | m=5x^2+7x-4 | | -6mx+3xy= | | 2x-x^3=-x | | (b+2+b)*(10b+20+b)=1204 | | 9x-6=3(3x-4) | | 3x(y-2m)= | | -55-(4x+5)=48 | | x^2+13x-156=0 | | -4x^2-29x-7=0 | | 4v^2+14v-60=0 |